The role of the adequacy of the owned capital in attracting bank deposits: An applied study of a group of commercial banks listed in the Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:The bank's capital is considered an essential element when establishing a commercial bank, as it is the main source of funding for all the bank's assets. In addition, it plays a crucial role in safeguarding the bank from operational or investment losses, as well as protecting customers' deposits from unexpected losses that the bank may incur. Based on this premise, the idea of the research began by elaborating on the concepts of owned capital in detail, as well as highlighting the importance of attracting deposits for commercial banks and the relationship between owned capital and deposit attraction in the bank. The research was limited to the indicators of capital adequacy ratio (capital to total assets, capital to total loans, and capital to total deposits) as independent variables, considering these indicators as the fundamental pillars on which depositors base their decisions to deposit their funds in commercial banks. The dependent variable was the total bank deposits during the research years. By adopting two banks, Babylon Commercial Bank and Iraqi Commercial Bank, as a purposive sample for the research and a time series spanning five years (2018-2022), the researcher assumes that there is a strong and statistically significant relationship and impact between the independent and dependent variables, and attempts to prove it using financial and statistical analysis. The researcher reached a set of conclusions, the most important of which is that the capital adequacy ratio to total deposits is the most influential indicator in attracting depositors' funds, as the primary demand of depositors is to provide sufficient protection for their funds during financial crises. There was also a set of recommendations, the most important of which was to strengthen the relationship between commercial banks and customers in order to ensure customers' trust and attract their deposits by using all necessary means of attraction.